Trading sex for shampoo: exploring machismo in police officers and female offenders’ experiences and perceptions of police sexual misconduct - Romo Pérez, Andrea (Policing and society, 2021)
Police sexual misconduct (PSM) is often referred to as hidden offenses because they are normally unreported. Most of the literature on the topic focuses on the sexual harassment experiences of policewomen. The media is increasingly reporting female civilians who have been affected by this form of police deviant behaviour. However, little is known about the experiences of female serious offenders with police sexual harassment and other forms of PSM. This study will examine how machismo in the Latin American country of Ecuador manifests in police officers and female offenders’ accounts and perceptions of PSM. Women’s responses to this form of police deviance will also be discussed. It was found that, according to both police officers and female offenders, consensual sex (even when both police and detainees referred to some sexual acts as consensual because no physical force was used, such sexual activity cannot truly be considered consensual given the unequal power dynamic and lack of basic resources available to female detainees.) was common in police detention centres. The encounters resulted in women receiving certain benefits. Police officers typically avoided their responsibility or that of their colleagues in the perpetuation of this behaviour. Machismo and the lack of supervision in police detention facilities are two factors influencing this behaviour in Ecuador.